« Après Xynthia… je ne suis pas inquiet, moi, la mer, ça ne me fait pas [peur]… »Du déni à l’adaptation. Les viticulteurs de l’île de Ré face aux changements environnementaux - Camille Hochedez; Benoît Leroux (Développement Durable et Territoires)
This paper investigates Ré Island wine growers' perceptions of environmental change, more specifically climate change, and how this brings about a change – or not – in their agricultural practices. Our results show that while they clearly perceive medium-term changes, they are largely unaware of the challenges and vulnerabilities associated with long term changes, which tend to be viewed in a positive light. In effect, their practices do not substantially evolve over time. The island’s professional, political and touristic context shields them from the potentially negative effects of environmental change.